2015
DOI: 10.1093/bja/aeu401
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of closed-loop co-administration of propofol and remifentanil guided by the bispectral index in obese patients: a prospective cohort comparison

Abstract: NCT00779844.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In contrast to dexmedetomidine, they found no sparing effect on both drugs when adding nitrous oxide to the anaesthetic regimen [48]. They also studied the feasibility of their system to determine propofol and remifentanil requirements during general anaesthesia in obese and lean surgical patients and concluded that the amount of propofol-remifentanil administered by the closedloop controller is consistent with current knowledge; propofol is best dosed using total body weight, whereas remifentanil is best dosed using ideal body weight [49]. In children and adolescent patients, their closed-loop system outperformed skilled manual control of propofol and remifentanil [50].…”
Section: Closed-loop Controlmentioning
confidence: 70%
“…In contrast to dexmedetomidine, they found no sparing effect on both drugs when adding nitrous oxide to the anaesthetic regimen [48]. They also studied the feasibility of their system to determine propofol and remifentanil requirements during general anaesthesia in obese and lean surgical patients and concluded that the amount of propofol-remifentanil administered by the closedloop controller is consistent with current knowledge; propofol is best dosed using total body weight, whereas remifentanil is best dosed using ideal body weight [49]. In children and adolescent patients, their closed-loop system outperformed skilled manual control of propofol and remifentanil [50].…”
Section: Closed-loop Controlmentioning
confidence: 70%
“…The input signal is in all cases derived from the electroencephalographic signal (EEG), the BiSpectral Index ® (Aspect Medical Systems, MA) in some cases [9,39,40], the EEG M-Entropy (GE HealthCare) [41] Technology Co., Ltd., Guangxi, China) [7] is already CE marked and commercially available. All these closed-loop controllers have been developed in order to adapt the propofol administration flow rate to obtain a target EEG index (BIS, SE or Neurosense) value around 50.…”
Section: Closed-loop Propofol Administrationmentioning
confidence: 99%
“…Two devices have already been validated: EasyTIVA ® (Medsteer ® , Suresnes, France) [8,9] and McSleepy ® (McGill university, Québec, Canada) [44]. The analgesic targets differ between these two devices: EasyTIVA ® targets specific changes in a EEG-derived signal that has been related to nociception during surgery under propofol anaesthesia [39], and hence infers therapeutic changes implemented by an automated syringe pump administering a short acting opioid: remifentanil [51].…”
Section: Closed-loop Opioid Administrationmentioning
confidence: 99%
See 2 more Smart Citations